2012
DOI: 10.1016/j.jalgebra.2011.10.042
|View full text |Cite
|
Sign up to set email alerts
|

The freeness and minimal free resolutions of modules of differential operators of a generic hyperplane arrangement

Abstract: Let A be a generic hyperplane arrangement composed of r hyperplanes in an n-dimensional vector space, and S the polynomial ring in n variables. We consider the S-submodule D(m)(A) of the nth Weyl algebra of homogeneous differential operators of order m preserving the defining ideal of A. We prove that if n ≥ 3, r > n, m > r - n + 1, then D(m)(A) is free (Holm's conjecture). Combining this with some results by Holm, we see that D(m)(A) is free unless n ≥ 3, r > n, m < r - n + 1. In the remaining case, we constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Let A be a generic ℓ-arrangement. Then A is m-free if and only if m ≥ n − ℓ + 1 [6]. The "if" part of this result coincides with Theorem 4.3 when ℓ = 3.…”
Section: L(supporting
confidence: 74%
See 1 more Smart Citation
“…Let A be a generic ℓ-arrangement. Then A is m-free if and only if m ≥ n − ℓ + 1 [6]. The "if" part of this result coincides with Theorem 4.3 when ℓ = 3.…”
Section: L(supporting
confidence: 74%
“…Holm [2] asked whether all arrangements are m-free for m large enough. It is shown that generic ℓarrangements (i.e., every ℓ hyperplanes of A intersect only at the origin) are m-free if and only if m ≥ n − ℓ + 1 [2,6]. This means that the Holm's question is true for generic arrangements.…”
Section: Introductionmentioning
confidence: 99%
“…We say that A is generic if |A | > ℓ ≥ 3, and if every ℓ hyperplanes of A intersect only at the origin. For a generic arrangement A , it is shown in [7] that A is m-free if and only if m ≥ |A | − ℓ + 1. On the other hand, the behavior of m-freeness has not been well analyzed yet when m ≥ 2.…”
Section: Resultsmentioning
confidence: 99%